From digital advocacy to age reduction legislation, the story of Nigeria’s #nottooyoungtorun (2021)
The #NotTooYoungToRun, a global campaign to expand youth inclusivity in politics. The Nigerian campaign, championed by the Youth Initiative for Advocacy, Growth and Advancement (YIAGA), employed both digital and offline advocacy to demand a reduction in the constitutional age limit for contesting elections in the country. With the aim of making politics, especially the right to be voted for, more accessible for young people. This paper employed qualitative content analysis of 904 manually purposively selected tweets from the #NotTooYoungToRun Twitter hashtag. Six dominant themes: victory/inspirational youth movement, activism, youth participation, solidary/endorsement, partisan bickering, and ageism. The context of the representative tweets were provided by exemplar tweets provided under each theme. The finding revealed that Nigerian youths demanded and achieved the signing of the 2018 Age Reduction Act. This victory was based on a systematic social media campaign in which the youths advanced their message. In so doing, they set public agenda by getting influential young Nigerians to either endorse their message or/and highly placed publicly show their solidarity. In addition, Nigerian youths engaged politicians who pushed the legislation through parliament, until it was signed into law by the Nigerian president. The #NotTooYoungToRun campaign is an exemplar of how youth driven movements have harnessed digital media for social and political change.